Unlocking the Power of Magnesium: A Systematic Review and Meta-Analysis Regarding Its Role in Oxidative Stress and Inflammation - Violeta Cepeda; Marina Ródenas-Munar; Silvia García; Cristina Bouzas; Josep A. Tur (Antioxidants)
Magnesium plays a crucial role in over 300 enzymatic reactions related to energy production, muscle contraction, and nerve function. Given its essential biological functions and increasing prevalence of suboptimal intake, magnesium supplementation has gained attention for its potential health benefits, particularly in mitigating oxidative stress and inflammation. This systematic review and meta-analysis aimed to evaluate the antioxidant effects of dietary and supplemental magnesium on several biomarkers related to oxidative stress and inflammation. A systematic search of studies published from 2000 to 2025 identified 28 relevant articles, including both animal and human studies. The meta-analysis assessed the effects of magnesium supplementation on oxidative stress biomarkers such as nitric oxide (NO), total antioxidant capacity (TAC), malondialdehyde (MDA), glutathione (GSH), and C-reactive protein (CRP). While results showed a statistically significant reduction in CRP levels, suggesting an anti-inflammatory effect, no conclusive impact on oxidative stress biomarkers was observed. The findings highlight magnesium’s potential role in inflammation regulation, though its direct antioxidant effects remain uncertain. Further high-quality clinical trials are needed to clarify the impact of magnesium supplementation on oxidative stress and to explore its broader health implications.